ANALISIS AKAD IJARAH MUNTAHIYA BITTAMLIK DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Munif, Nasrulloh Ali (Ahkam: Jurnal Hukum Islam, 2016)
The fast growing of shariah financial industry has forced the practioners and academist of shariah banking to be more innovative to meet the demand. One of the innovation is the settlement of new agreement called Ijarah Al Muntahiya bit Tamlik (financial leasing with purchase). This agreement is a hybrid transaction which combines leasing and ownership in the end of the leasing. This innovation has turned to give some benefit and advantages. However, the legal basis of its operation, both from the Islamic perspective and the Indonesian positive law, is being questioned. Anyway, from the perspective of Islamic law Ijarah Muntahiya Bittamlik has fulfilled the requirement and three criteria of legal transaction even though there is a different opinion saying that it may belong to the join transaction (murakab) which is forbidden by the Prophet. The majority of Islamic jurists come to their common agreement that Ijarah Muntahiya Bittamlik is allowed. From the perspective of Indonesian positive law, Ijarah Muntahiya Bittamlik belongs to anonymous agreement (article 1319) which emerges due to the freedom to settle an agreement (article 1338) and Ijarah Muntahiya Bittamlik has fulfilled the criteria of a legal transaction (article 1320) and the components of a transaction. The legal impact of Ijarah Muntahiya Bittamlik is the rights and the responsibilities of the parties involved. Kata kunci: Ijarah Muntahiya Bittamlik, Hukum Islam, Hukum positif